The effectiveness of the brainstorming technique toward enhancing creative and critical thinking skills among secondary Iraqi physics students / Farah M.R. Hamza Alrubai - Alrubai, Farah M.R. Hamza (2014)

(untitled)
Past research has established that Iraqi education lacks integration of creative and critical thinking skills in the classroom. Thus, the main purpose of this study was to investigate the effectiveness of the brainstorming technique towards enhancing creative and critical thinking skills among secondary Iraqi physics students. First, the existing procedures for the brainstorming technique which comprised three original steps, problem identification, idea generation and idea evaluation were identified through a literature review. Three new steps, namely selection of the best idea, implementation and problem solving were added in this study. A mixed-method methodology was employed in the study. For the quantitative aspect, a quasi-experimental design was utilised. A total of 80 students from two intact classes in the Iraqi Saba School participated in the study. One class was taken as the control group (N = 41) who were taught physics via the traditional method while the other class was the experimental group (N = 39) who were taught physics via the brainstorming technique for four months. The Physics achievement test was prepared specifically for this study for the purpose of establishing homogeneity between the control and experimental groups. The independent variable was the method of instruction, either the brainstorming technique or traditional method. The dependent variables were performance in creative and critical thinking tests. The Torrance Test of Creative Thinking (TTCT) and the Watson Glaser Critical Thinking (WGCT) were modified and adapted to measure the respective dependent variables. The problem solving tasks in these tests were based on four physics topics namely, reflection of light, refraction of light, thin lenses, and color and electromagnetic spectrum. In the TTCT, there were three dimensions of creative thinking, fluency, flexibility and originality. For the WGCT, the five dimensions were inference, recognizing assumptions, deduction, iv interpretation and evaluating arguments. Additionally, students’ perceptions about the brainstorming technique were captured through qualitative interviews and open-ended questionnaires. Results of the t-test showed that the experimental and control groups were equal in the TTCT, WGCT and in physics achievement tests before the intervention. After the four months intervention, results of the multivariate analysis of variance (MANOVA) and analysis of covariance (ANCOVA) showed that there were significant differences in creative thinking overall and in the sub skills of fluency, flexibility, and originality between the groups. Results for the critical thinking test showed that there were statistically significant differences in critical thinking overall and in the sub skills recognizing assumptions, interpretation, and evaluating arguments between the groups. However, analysis showed there was no significant difference for the two sub skills of critical thinking which were inference and deduction skills. The study revealed that the brainstorming technique could create scaffolds for the enhancement of creative and critical thinking, as the students proceeded through the various steps of the technique. Furthermore, students characterized brainstorming as an effective teaching technique for learning physics. Nonetheless, the Iraqi students also suggested several ideas to improve the brainstorming technique for the teaching and learning of physics.